Depiction of Role and Power in EFL Teachers’ Lesson Plans - Safria Rima Jayusna; Yuni Utami Asih; Bibit Suhatmady (PT ARRUS Intelektual Indonesia, 2022)
An effective lesson plan that includes a variety of mutual activities between students and teacher is required for the instructional process. The lesson plan, on the other hand, is not intended to guide students to be more independent during the process or to apply student-centered learning. As a result, this research is being conducted to examine the role and authority displayed on the twelfth-grade teachers’ lesson plan. This research is closely connected to critical discourse analysis, which utilises Brooks' idea of 'Role and Power' (2015). According to the evaluation of the lesson plans, the teachers play a prominent role during the instructional process. On the one hand, they have greater authority in their duties as a teaching manager, guide, and facilitator. For example, according to the lesson plan, the teachers have a prominent role in leading and questioning the students during the teaching and learning process, as represented on the lesson plans. In this situation, the teachers identify as the dominating figure to carry out their tasks in the educational process.